2023
DOI: 10.1111/joa.13889
|View full text |Cite
|
Sign up to set email alerts
|

Hyper‐reflective dots in optical coherence tomography imaging and inflammation markers in diabetic retinopathy

Abstract: The aim of this study is to correlate small dot hyper‐reflective foci (HRF) observed in spectral domain optical coherence tomography (SD‐OCT) scans of an animal model of hyperglycaemia with focal electroretinography (fERG) response and immunolabelling of retinal markers. The eyes of an animal model of hyperglycaemia showing signs of diabetic retinopathy (DR) were imaged using SD‐OCT. Areas showing dot HRF were further evaluated using fERG. Retinal areas enclosing the HRF were dissected and serially sectioned, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, hyperreflective foci observed in our patient's OCT may confirm the presence of activated macrophages and microglia, as suggested by several studies. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperreflective foci observed in our patient's OCT may confirm the presence of activated macrophages and microglia, as suggested by several studies. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of microglia activity in vivo is limited by the expansive and complex methodology (i.e., PET-MRI) needed ( 18 , 19 ). Recently, OCT was demonstrated to be able to identify HRF, nodules of activated microglia, in the inner retina, ( 6 ). In previous studies, we investigated the association of HRF with inflammatory parameters and found a strong correlation with cortical demyelination ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optical Coherence Tomography (OCT) allows to study in vivo retinal microglia activation ( 6 ). Indeed, it has been recently demonstrated in an animal model of diabetes that focal Blood-Retina-Barrier (BRB) damage strongly associate with retinal microglia proliferation, and the histologically defined pattern corresponded to the hyper-reflective foci (HRF) observed by OCT ( 6 ). Thus, HRF has been proposed as in-vivo biomarker of microglia proliferation.…”
Section: Introductionmentioning
confidence: 99%